Pengaruh Etika Marketing Terhadap Keputusan Nasabah Menggunakan Produk Murabahah Perspektif Hukum Islam Di BPRS Tulen Amanah - H. Zainal Arifin Haji Munir; Selamat Muliadi (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the influence of Islamic Marketing ethics on customer decisions in financing murabahah at BPRS Tulen Amanah Paok Motong, East Lombok. The Number of Samples used in this study amounted to 93 respondents. The research used the quantitative with correlation method. The data source was observations, questionnaires and documentations. The analyzing of the data used IBM SPSS Statistics version 25. Analysis was carried out by several tests, sucs as validity test, realibility test, normality test, heteroscedasticity test, linearity test, linear regression analysis and coefficient of determination test. The results showed that the imfluence of Islamic marketing ethics on customer decisions are evidenced by a significance value of 0.021 < 0.05 and tcount of 2.357 > 1.986 (ttable), Ha is accepted and Ho is rejected. Which means that the Islamic marketing ethics significantly influences customer decisions in financing murabah at BPRS Tulen Amanah Paok Motong, East Lombok. The value of R2 (R Square) 0.058 or equal to 5.8%. The value means that the Islamic Marketing ethics variable has a tendency of the percentage of influence or correlation to the dependent variable in customer decisions of 5.8% from 100%. While the rest (100% - 5.8% =94.2%) is influenced by other variables outside of this refression.